The Influence of Bearing Clearance on the Load Capacity of Gas Polymer Bearings - Gregor Schilling; Robert Liebich (Applied Sciences, 2023)
In this paper, the influence of a nominal bearing clearance on the lift-off behaviour and the load-carrying capacity of gas polymer bearings (GPBs) is investigated. For this purpose, an experimental study with five different bearing gap configurations and a range of static loads is carried out. Furthermore, the test rig for the clearance and friction torque measurements is illustrated and discussed from a practical point of view. The experimental gap measurement results of all the bearing configurations and the method used are explained and discussed. Finally, the friction torque during the lift-off and run-up phases is measured for a range of static loads. A method that uses the time derivative of the measured friction torque during the run-up tests as a criterion for the lift-off detection is explained and applied to the measured data. The results of this study indicate that there are large differences between the most studied bump-type and gas polymer bearings in terms of the dependence of the load-carrying capacity on the bearing gap. Furthermore, the recorded effects are described, and possible explanations are given. Finally, the differences in characteristics from those of bump-type bearings are described and their importance for the design process of rotors supported in GPBs is explained.